2012
DOI: 10.1111/ijlh.12023
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fragmented red cell (FRC) counting using Sysmex XE‐5000 – Does hypochromia play a role?

Abstract: Despite the agreement between FRC count and the manual method, the overvaluation of FRC was high, leading to false-positive results. Microcytosis appeared to have no impact on FRC count, whereas mild hypochromia seemed to be related with FRC count. Particular attention is required to assess automated FRCs in samples with mild hypochromia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 19 publications
(36 reference statements)
2
18
0
Order By: Relevance
“…Jiang et al reported that the FRC count by the Sysmex XE‐2100 was spuriously high in samples taken from patients with iron deficiency anaemia. In contrast, previous studies using the Sysmex XE‐5000 and XN‐9000 devices have reported that an increased number of microcytic RBCs did not interfere with the FRC count, which is similar to the result we observed in our thalassaemia group. The reason for this difference between studies may be improvement in the function of subsequent generations of automated analysers.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Jiang et al reported that the FRC count by the Sysmex XE‐2100 was spuriously high in samples taken from patients with iron deficiency anaemia. In contrast, previous studies using the Sysmex XE‐5000 and XN‐9000 devices have reported that an increased number of microcytic RBCs did not interfere with the FRC count, which is similar to the result we observed in our thalassaemia group. The reason for this difference between studies may be improvement in the function of subsequent generations of automated analysers.…”
Section: Discussionsupporting
confidence: 85%
“…This study is the first to compare schistocyte detection and quantification by the Sysmex XN series with that of the gold standard microscopy method in blood samples taken from patients suspected of having schistocytosis. Previous studies either researched FRC count by the Sysmex XE series (XE‐2100 and XE‐5000) in heterogeneous groups of patients, or studied the FRC reference range using an XN‐9000 in healthy patients . We found that when using the analyser in the samples derived from the group of patients suspected of having schistocytosis, it could discriminate between presence and absence of schistocytosis reasonably well, as evidenced by the AUC of the ROC curve being more than or equal to 0.8 (AUC = 0.803; 95% CI, 0.689‐0.917) .…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Certainly the FRC count does not represent an automated count of schistocytes only, and if a precise schistocyte evaluation is needed, a film review is needed. However, in studies of adults, automated and manual values tended to correlate well [5,[23][24][25]. Also, we had relatively few very premature neonates in our database.…”
Section: Discussionmentioning
confidence: 88%